Comparative analysis of peripheral blood circulation parameters in long-distance swimmers at middle altitude and under the conditions of a hypoxic gas environment - Bolotin, A.; Bakayev, V. (SportMont, 2020)
Competitive activity at middle altitude creates increased demand on the cardiovascular system of long-distance swimmers. The state of their cardiovascular system and its readiness for such activities at middle altitude can be evaluated according to haemodynamic parameters. At the same time, state-of-the-art strategies for cardiovascular disorder prevention in long-distance swimmers during training for competitive activity at middle altitude are mostly based on the assessment of systemic haemodynamics, with no reference to microcirculation. The process of adaptation and changes in the functional parameters of long-distance swimmers that characterize their physical performance and the function of external respiration mainly occurs by broadening the range of training tools and methods. The unrestricted broadening of these tools and methods can cause severe disturbances in the functioning of the cardiovascular system. At the same time, existing methods for assessing the state of the cardiovascular system in long-distance swimmers do not allow performing a qualitative evaluation of the peripheral circulation haemodynamic parameters. The studies conducted have shown that microcirculation parameters in long-distance swimmers at different training loads have similar dynamics at middle altitude and under the conditions of a hypoxic gas environment, which allows for higher quality assessment of the cardiovascular system state in athletes and for the more accurate evaluation of their bodily reaction to different training loads at middle altitude.